Implementasi Metode Tebak Kata dalam Meningkatkan Keterampilan Berbicara Siswa - Irma Sari Daulay; Sutan Botung Hasibuan; Indah Sri Rahayu Pasaribu (Indo-MathEdu Intellectuals Journal, 2023)
Speaking skills play an important role in giving birth to a future generation that is intelligent, creative, critical and cultured. Through mastery of speaking skills, students are able to express their thoughts intelligently according to the material and situation when they are speaking. The aim of this research is to find out how the implementation of the word guessing method improves students' speaking skills. The type of research used is classroom action research (PTK) with two cycles. The research subjects were 25 people consisting of 11 men and 14 women. Data collection techniques in this research were obtained through observation and tests. The research results obtained in cycle I were 4 students or 16.00% "very good" speaking skills, 13 students or 52.00% "good" speaking skills, 8 students or 4.00% "fair" speaking skills, none students' speaking skills were "poor", and there were no students with "very poor" speaking skills, in cycle II there were 15 students or 60.00% "very good" speaking skills, 10 students or 40.00% "good" speaking skills, no there were students with "fair" speaking skills, no students with "poor" speaking skills, and no "very poor" speaking skills. So it can be concluded that the word guessing method can improve the speaking skills of class IV students at SD Negeri 0508 Tangga Bosi